Obesity as a Risk Factor for Cardiovascular Diseases - o'g'li, Naimov Dilshod Qayim (Journal of Science in Medicine and Life, 2024)
Currently, obesity is becoming a “non-infectious pandemic”. According to a large number of epidemiological studies, a connection has been established between the increase in the prevalence of the pathology under discussion and the increase in the number of other diseases. In obese patients, the risk of developing cardiovascular diseases increases several times. It is known that the incidence of arterial hypertension, coronary heart disease, heart failure, hypercholesterolemia, blood rheology disorders, and thromboembolic complications increases in patients with this disorder. This article discusses the effect of obesity on the cardiovascular system.